The Shelf-Life Prediction of Black Garlic Chili Sauce and “Cahyo” Garlic Chili Sauce with Accelerated Shelf-Life Testing (ASLT) Method Based on The Arrhenius Model - Afridho Laksono Indra Purnama; Ratna Yulistiani; Luqman Agung Wicaksono; Wahyu Setyarini; Radita Yuniar Arizandy; Nadya Dwi Putri Febrianti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Sambal is often found in various menu variants served in the Indonesian food industry; this is a supporting factor for creating bottled chili sauce. In this research, fermented black garlic chili sauce was made with black garlic as raw material to provide added value in the form of antibacterial and antioxidant compounds, as well as giving a novelty value to the product as well as a differentiator in the elements of color, aroma, consistency, and taste of the product. The final product consumers receive is compared to "Cahyo" garlic chili sauce produced by PT. Deltasari Indah Restaurant. Sambal contains oil/fat, which is quickly rancid, thus affecting the element of consumer acceptance. Therefore, it is necessary to predict the shelf life of bottled chili products. This research aims to predict the shelf life of the black garlic chili sauce and “Cahyo” garlic chili sauce products in bottles produced by PT. Deltasari Indah Restaurant with the ASLT method, the Arrhenius model approach; Knowing the difference in the shelf life of bottled chili products stored at different temperature conditions; and determining the proper temperature and storage conditions to get the maximum shelf life for packaged chili products. This study uses the Accelerated Shelf-Life Testing method with the Arrhenius model. Based on the pH value parameter, the shelf life of black garlic chili sauce was 33 days, and “Cahyo” garlic chili sauce was 45 days. These two results are the results of the shelf life obtained from calculations at 20˚C and 25˚C then the average value is taken.